Influence of soil porosity on hydraulic properties in dike failure induced by overtopping - Hao Wu; Kunpeng Zhao (Scientific Reports)
Abstract Coastal dike failures can lead to severe disasters. However, the impact of soil porosity on hydraulic properties during sea-dike failure induced by overtopping has not been adequately studied. This research develops a numerical simulation method to model sea-dike failure and analyze the influence of soil porosity on hydraulic properties during dike failure. A sediment scour model for bedload and suspended load is employed to simulate soil erosion during dike breaching. The Reynolds-averaged Navier–Stokes equations are used to characterize the hydrodynamic properties of breach flow. The results indicate that the breach process of cohesionless dikes can be generally categorized into three stages: lateral erosion of the dike crest, downstream slope erosion, and vertical erosion of the dike crest. The denser the dike, the less susceptible it is to failure, and the longer the breach duration, the larger the residual dike body. The variation in porosity does not affect the dike breach duration or the time of peak flow arrival, but it does influence the peak flow magnitude. The relationship between dike porosity and peak flow rate exhibits a significant positive linear correlation. This research enhances the understanding of the sea-dike failure process and contributes to disaster prevention and mitigation in coastal areas.